Clamshell incision plus full sternotomy as a complex approach to complicated aortic arch aneurysm - Polo-Gutiérrez, Gerber (2022)
Surgical treatment of aortic arch aneurysm is one of the greatest challenges of aortic surgery. We present a young woman with Marfan syndrome, severe Excavated Pectus and previous Bentall procedure, who underwent emergency surgery for ruptured aortic arch aneurysm. We achieved a successful approach through a Clamshell incision associated with a median re-sternotomy.